Numerical Prediction of Total Resistance Using Full Similarity Technique - Sezen, Savas; Cakici, Ferdi (CHINA OCEAN PRESS, 2019)
Model tests are often conducted by researchers in a real or a numerical towing tank to calculate residuary resistance of a ship with the aid of Froude similarity. Common ITTC-1957 formula is usually employed to calculate frictional resistance. As computer technologies develop over time, CFD tools are used for calculating total resistance of a ship at full scale without establishing any dynamic similarities. In this paper, both Froude and Reynolds similarities are numerically implemented to four different model scales by using virtual fluids. The total resistance at different Fr numbers calculated by the numerical study is validated against the experimental data of DTMB 5512 (L=3.048 m) model hull. The results show that establishing Froude and Reynolds similarities together in numerical simulation is possible in principle. To determine whether it has advantages for prediction of full-scale ship total resistance by employing this method, it is also examined the model scale with the same number of elements and Reynolds number of the full-scale ship. Results show that numerical calculation of total resistance for a full-scale ship in a model scale by defining virtual fluids has only slight advantages on the prediction of residuary resistance. Additionally, no advantage in the calculation of frictional resistance is observed.
Keywords: total resistance; Froude and Reynolds similarities; DTMB 5512; CFD; CFD SIMULATIONS; SCALE SHIP; VERIFICATION; VALIDATION; MODEL; Engineering; Water Resources